Key to Ooctonus Haliday (Hymenoptera: Mymaridae) in China, with one new species and three new country records - Aishan, Zhulidezi; Triapitsyn, Serguei V.; Zhu, Chao-Dong; Hu, Hong-Ying (Zootaxa, 2022)
A new species of Ooctonus Haliday (Hymenoptera: Mymaridae), O. innermongolicus Aishan & Hu sp. nov., is described from Inner Mongolia and Tibet, China. Eight other species of the genus, including the three new records O. hemipterus Haliday, O. lokomotiv Triapitsyn and O. spartak Triapitsyn, are also reported and illustrated. A key to females is provided for the 18 species of Ooctonus known from China.